2012
DOI: 10.1002/adv.21296
|View full text |Cite
|
Sign up to set email alerts
|

Adding Autonomic Healing Capabilities to Polyethylene Oxide

Abstract: The addition of autonomic healing (frequently defined as self-healing) capabilities to a water-soluble polymer (polyethylene oxide, PEO) is for the first time reported. The self-healing system consists of urea-formaldehyde microcapsules filled with dicyclopentadiene and first-generation Grubbs catalyst, dispersed within polyethylene oxide. Raman spectroscopy, optical microscopy, electron microscopy, and thermogravimetric analysis were used to characterize

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The early extrinsic microcapsule-based self-healing systems consisted mainly of healing agent-containing microcapsules and catalyst particles dispersed directly into matrices. , The healing agent, when released from the broken microcapsules along the formation of cracks, would flow into the cracks and subsequently repair them via polymerization with the catalyst. However, catalysts embedded directly into the coatings always suffer from a fatal issue: the possibility of deactivation due to chemical reactions with the coating matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The early extrinsic microcapsule-based self-healing systems consisted mainly of healing agent-containing microcapsules and catalyst particles dispersed directly into matrices. , The healing agent, when released from the broken microcapsules along the formation of cracks, would flow into the cracks and subsequently repair them via polymerization with the catalyst. However, catalysts embedded directly into the coatings always suffer from a fatal issue: the possibility of deactivation due to chemical reactions with the coating matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Chipara et al reported the introduction of DCPD-filled polyurea formaldehyde microcapsules and FGGC Grubbs' catalyst into polyethylene oxide (PEO). [41] Again, an external mechanical stimulus breaks the capsules that start to leak DCPD. The presence of the catalyst triggers the polymerization process and the so formed poly(dicyclopentadiene) (PDCPD) heals the macroscopic fracture of PEO matrix.…”
Section: Microcapsulesmentioning
confidence: 99%
“…After the first successful self‐healing study with the DCPD/Grubbs catalyst system, several attempts were surfaced to create a feasible self‐healing systems for real structural application. Due to the several drawbacks of the DCPD/Grubbs such that Grubb's catalyst is rather expensive and degraded by the amine‐based catalyst of matrix, it is important to develop sustainable and cost‐effective self‐healing materials where Grubb's catalyst is replaced by a new catalyst system.…”
Section: Introductionmentioning
confidence: 99%